Effects of acupuncture on gut microbiota and short-chain fatty acids in patients with functional constipation: a randomized placebo-controlled trial - Yan, Xiang-Yun; Yao, Jun-Peng; Li, Yan-Qiu; Xiao, Xian-Jun; Yang, Wan-Qing; Chen, Si-Jue; Tang, Tai-Chun; Yang, Yu-Qing; Qu, Liu; Hou, Yu-Jun; Chen, Min; Li, Ying (Frontiers in Pharmacology, 2023)
Objective: To comprehensively evaluate the effect of acupuncture on gut microbiota, identify specific microbes closely related to the clinical efficacy of acupuncture, and explored the role of short-chain fatty acids (SCFAs).: A randomized placebo-controlled trial was conducted with 80 FC patients and 28 healthy controls (HCs). FC patients randomly received 16 acupuncture (n = 40) or sham acupuncture (n = 40) sessions over four weeks; HCs received no treatment.The change in the proportion of patients with mean weekly complete spontaneous bowel movements (CSBMs) was considered as the primary outcome measure.Moreover, the composition and the predictive metabolic function of the gut microbiota from feceal samples were analyzed by 16S rRNA gene sequencing, while feceal SCFAs were identified via gas chromatography-mass spectrometry (GC-MS).Results: Compared to sham acupuncture, acupuncture significantly increased the proportion of CSBM responders, and improved spontaneous bowel movements (SBMs), straining, stool consistency, and quality of life. Moreover, Sequencing of 16S rRNA genes revealed that acupuncture improved β-diversity and restored the composition of gut microbiota. Specifically, the abundance of beneficial bacteria such as g_Lactobacillus increased while that of pathogenic bacteria such as g_Pseudomonas decreased after acupuncture, which were significantly correlated with alleviated symptoms. Moreover, ten microbes including g_Coprobacter, g_Lactobacillus, and g_Eubacterium_coprostanoligenes_group might be considered acupuncture-specific microbes, and formed a stable interaction network. Additionally, GC-MS analysis indicated that acupuncture increased the content of butyrate acid in the gut, which was positively correlated with an increase in defecation frequency and a decrease in acupuncture-related pathogens. Finally, acupuncture specific-microbes including g_Coprobacter, g_Lactobacillus, g_Pseudomonas, g_Eubacterium_coprostanoligenes_group, g_Erysipelotrichaceae_UCG.003, g_Prevotellaceae_UCG.001, and g_Rolstonia could accurately predict the clinical efficacy of acupuncture (AUC = 0.918). Conclusion: Acupuncture could effectively improve clinical symptoms in FC patients, and was associated with gut microbiota reshaping and increased butyrate acid levels. Moreover, key microbial genera such as g_Coprobacter and g_Lactobacillus was predictive of acupuncture efficacy in treating FC. Future studies are required to 5386 删除[WPS_244856236]:validate the causal relationship between key microbial genera and acupuncture clinical efficacy, and should explore further metabolic pathways for designing personalized treatment strategies.